Meta-analysis of the effects of essential oil as an alternative to monensin in diets for beef cattle - Torres, R. N.S. [UNESP]; Paschoaloto, J. R.; Ezequiel, J. M.B. [UNESP]; da Silva, D. A.V.; Almeida, M. T.C. (Elsevier, 2021)
Additives used to improve feed efficiency of beef cattle on high-grain diets requires products that not only increase animal performance but also provide food safety for consumers. Since phytogenic additives such as essential oils (EO) are the main substitutes for monensin in the diet of cattle fed high-grain diets, this study aimed to evaluate, through meta-analysis, the effects of EO as an alternative to monensin in diets for beef cattle on feed intake, performance, carcass characteristics and ruminal fermentative parameters. Ten peer-reviewed publications with 27 treatment means were included in the data set. These effects were evaluated using random-effect models to examine the weighted mean differences (WMD) between EO treatment and control treatment (diets with monensin). Heterogeneity was explored by meta-regression and subgroup analysis. The substitution of EO for monensin did not affect methane production, ruminal pH values, average daily gain, feed efficiency or carcass weight. However, carcass dressing percentage (WMD = 0.38%; P = 0.03), ribeye area (WMD = 0.82 cm2; P < 0.0001) and subcutaneous fat thickness (WMD = 0.56 mm; P < 0.0001) values increased. Although the use of EO instead of monensin had no influence on the performance of beef cattle fed high-grain diets, the prevalence of hepatic abscesses increased 84.9% and the replacement of monensin by EO increased the risk ratio of hepatic abscess prevalence by 107%. Therefore, the use of EO in high-grain beef cattle diets was ineffective in protecting the liver against abscesses.
Keywords: Antibiotic; Feedlot; Functional oils; Liver abscess; Performance